Psikologi Islami solusi Islam atas problem problem psikologi - Jamaludin Ancok (Pustaka Pelajar, 1994)
ws.c.1/ast c.2/ir,c.3/ir,c.4/TR,C.5/tr,c.6/tr,c.7/tr,c.8/tr,c.9-13,14/oen, c.15/ir,c.16-19/en, c.20-28/